Low grain sink activity imposed by potassium deficiency aggravates loss in quality of rice (Oryza sativa L.) infected with natural sheath rot disease. (May 2019) - Zhang, Jianglin; Pan, Yonghui; Li, Yuwei; Ren, Tao; Cong, Rihuan; Lu, Jianwei; Li, Xiaokun
Abstract: This study investigated the effects of grain sink activity regulated by potassium (K) nutrition during sheath rot disease (ShR) infection on rice milling and appearance quality. We quantified the instantaneous grain sink activity and showed that K application had no significant effects on rice milling and appearance quality in the absence of ShR infection. However, K deficiency substantially aggravated the effects of ShR infection on rice quality, such as the rate of broken rice (RBR), and ShR infection notably increased the difference in milling and appearance quality between K-deficient and K-sufficient rice. Specifically, ShR infection and K deficiency contributed 42.2% and 34% to the loss in the quality of Shenliangyou No. 5814 and 52.8% and 27.4% to the loss in the quality of Minhui No. 63, respectively. These findings suggest that K supply is crucial for improving the initial and maximal grain sink activity and thereby alleviating the loss in milling and appearance quality caused by ShR infection. Highlights: Potassium (K) deficiency and sheath rot disease (ShR) infection both decreased rice quality by inhibition of sink activity. ShR infection dramatically increased the differences in quality of rice between K-deficient and K-sufficient grains. A sufficient K supply improved the maximum grain sink activity to alleviate the loss in rice quality.